2017
DOI: 10.1186/s12983-017-0199-8
|View full text |Cite
|
Sign up to set email alerts
|

Sequential social experiences interact to modulate aggression but not brain gene expression in the honey bee (Apis mellifera)

Abstract: BackgroundIn highly structured societies, individuals behave flexibly and cooperatively in order to achieve a particular group-level outcome. However, even in social species, environmental inputs can have long lasting effects on individual behavior, and variable experiences can even result in consistent individual differences and constrained behavioral flexibility. Despite the fact that such constraints on behavior could have implications for behavioral optimization at the social group level, few studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 60 publications
4
29
0
1
Order By: Relevance
“…This discrepancy could reflect differences in the stability of social effects experienced at these two different life stages. Socially-induced changes in aggression during adulthood are reversible (Alaux & Robinson 2007;Rittschof 2017;Shpigler et al 2017b), while effects induced during the pre-adult stages are relatively stable, present one week into adulthood, even when bees were kept in a common laboratory environment (Rittschof et al 2015a). Consistent with this hypothesis, the greatest degree of overlap between our gene expression results and previous aggression studies is with the shift in aggression associated with behavioral maturation in adult worker bees.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This discrepancy could reflect differences in the stability of social effects experienced at these two different life stages. Socially-induced changes in aggression during adulthood are reversible (Alaux & Robinson 2007;Rittschof 2017;Shpigler et al 2017b), while effects induced during the pre-adult stages are relatively stable, present one week into adulthood, even when bees were kept in a common laboratory environment (Rittschof et al 2015a). Consistent with this hypothesis, the greatest degree of overlap between our gene expression results and previous aggression studies is with the shift in aggression associated with behavioral maturation in adult worker bees.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study in honey bees showed that individuals exhibit different levels of social responsiveness, showing high or low levels of response to cues, whether or not these cues matched individual behavioral specialization (Shpigler et al 2017a). Similarly, chronic stress impacts how individuals respond to social cues in the context of aggression (Rittschof 2017). Behavioral variation could reflect individual variation in response thresholds to sensory stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One dish at a time, we introduced a foreign intruder bee to the group of six and observed aggressive interactions for 1 min. We made note of the most aggressive bee in the group, based on the amount of biting, abdomen flexion, and stinging directed toward the foreign intruder (Li‐Byarlay et al, ; Rittschof, ; Rittschof, Coombs, et al, ). We waited an additional 5 min following the 1 min observation period to shake the bees from the dish into a bag and knock them down on ice for dissection.…”
Section: Methodsmentioning
confidence: 99%
“…For all brain assessments presented here, we analysed whole brains, with all glands removed, following previous studies (Alaux et al, 2009;Rittschof and Robinson, 2013;Rittschof et al, 2014;Chandrasekaran et al, 2015;Rittschof, 2017). We first assessed whether the aggressive behavioral response that results from alarm cue exposure is correlated with a shift in brain mitochondrial respiration.…”
Section: Analysis Of Brain Mitochondrial Respiration Bee Collectionsmentioning
confidence: 99%